Unlocking the power of gamification: Alleviating reward-sensitivity in promotional interactions - Lee, Wangoo; Lu, Lu; (Robert) Li, Xiang (International journal of hospitality management, 2024)
This research introduces a gamification-induced reward-desensitization effect observed in hotel loyalty promotions. Guided by scope-insensitivity theory and the dual-process model of value evaluation, it specifically examines whether integrating gamification into loyalty programs can mitigate customers’ sensitivity to reward size and unfair preferential treatments based on loyalty status. Study 1 focuses on varying reward sizes, while Study 2 appraises loyalty status when preferential treatment toward other members is observed. Both studies demonstrate that gamification effectively dampens consumer sensitivities towards reward size and unfair preferential treatment. Cross-national validation further reinforces the universal impact of gamification and paves the way for future research. Aside from the well-known role of gamification in enhancing customer experiences and motivating specific actions, this research explores a novel aspect of gamification: the attenuation of reward sensitivity. In practice, gamification thus provides a viable business solution to overcome challenges in traditional reward-centric programs. •Gamification desensitizes customer focus on reward value and preferential treatment.•Gamification enhances loyalty outcomes, particularly with small (vs. large) rewards.•Preferential treatment to low-status members diminishes high-status members’ loyalty.